Genius of Uzbek Art - Lafasov, Urak Pazilovich (Journal of Learning on History and Social Sciences, 2024)
This article ("The Genius of Uzbek Art") provides information about the rich literary heritage of nations on Earth, the novel, which is considered a subgenre in literature, and six national schools of novel writing (English, French, German, Indian, Arabic, Russian, and Uzbek). It was also said that until the 20th century, the fields of language and literature were studied separately in scientific researches in the world, and this situation caused serious damage to the art of text. In order to eliminate this defect in science, the field of linguopoetics was formed, and linguopoetics studies the issue of creating an aesthetic effect of stylistically colored linguistic units in the artistic text. It is also explained that the main goal of the field of linguopoetics is to describe the artistic expression and aesthetic effect of stylistically colored lexical units in the text, and it is explained that linguopoetics works with artistic texts that are considered national spiritual wealth. In order to achieve this status, the artist must be able to feel the spirit of his nation, to be well aware of the folk art, to have a deep knowledge of the vocabulary of his mother tongue, to be able to understand and use the means of artistic representation at a high level, and only then the scope of expression of the national language and the level of incomparable image is emphasized. As a basis, the sound doubling, sound exchange, morphological forms, vocabulary units (synonyms, antonyms, pure Uzbek words, dialectal words, phraseology) used in the novel "Mehrobdan Chayan" by the great Uzbek writer Abdulla Qadiri, artistic arts (irony, simile, exaggeration, saj), lygvopoetic tools such as proverbs, portraits, replica-repetition were analyzed.